New perspetives on language policy for language revitalisation - O’Laoire, Muiris (Te Kaharoa, 2012)
Language revitalisation has always been, and continues to be about communal involvement, savvy and dedication. Language policy, on the other hand, is often crafted in isolation from the lived experience of the speech community. Language policy tends to be formulated in a regulatory landscape where fiscal arguments, inter-agency disputes and centralist thinking dominate. However, when policies emerge from the centre and when they are being implemented on the ground, the language community can play a significant role in modifying and localising them. This paper will shed new light on recent language policy research that highlights individual and collective agency in the processes of language use, attitudes and policies. Drawing on Pennycook’s theory (2010) of local practice, it will show that communities on the ground, charged with implementation are not the passive receivers of policies or the vague resistors once depicted in research account, but social actors who can exercise subaltern agency. This understanding of the way that the local has a bearing on the thinking and behaviour of agency on the ground is often overlooked by, or hidden from the policy maker’s centralist gaze.The aim is to show that language policies in language revitalisation and minority language contexts are not merely implemented, but are actually shaped on the ground.